O Estado de Minas Gerais e suas regiões: um resgate histórico das principais propostas oficiais de regionalização - Alexandre Magno Alves Diniz; Wagner Barbosa Batella (Sociedade & Natureza)
In lieu of the increasing importance of regional approaches in contemporary geography and theabsence of studies that synthesize and discuss the various regionalization proposals in vogue inMinas Gerais State, the present work identifies and scrutinizes, in light of major theoretical contri-butions on regional analysis, the various official regionalizations of Minas Gerais State, set forthover the last decades. The study starts with an explanation of the importance of the historicalevolution of regional approaches throughout the history of geographic thought, emphasizing itsmethodological dimension. Then, the official regionalizations of Minas Gerais State produced byFundação João Pinheiro (FJP) and by the Instituto Brasileiro de Geografia e Estatística (IBGE)are identified, mapped and discussed. The Physiographic, Functional, Micro and Meso, Planningand Administrative regions are emphasized.